Extraradical hyphae of the mycorrhizal fungus Glomus intraradices can hydrolyse organic phosphate - Koide, R T (The New phytologist, 2000)
Organic phosphorus sources make up a large fraction of the total P in some soils. Vesicular-arbuscular mycorrhizal fungi provide a large surface area for the absorption of inorganic P. The question of whether or not they have direct access to organic P by producing extracellular phosphatases has hitherto been controversial because experiments had not been performed in the absence of other soil microorganisms. We used a split-dish in vitro carrot mycorrhiza system free from contaminating microorganisms. The extraradical hyphae of Glomus intraradices hydrolysed both 5-bromo-4-chloro-3-indolyl phosphate and phenolphthalein diphosphate. Moreover, they transferred significantly more P to roots when they had access to inositol hexaphosphoric acid (phytate) than when they did not. Thus we show unequivocally that extraradical hyphae of G. intraradices can hydrolyse organic P, and, further, that the resultant inorganic P can be taken up and transported to host roots